The Emerging Role of Microglia in Neuromyelitis Optica - Chen, Tingjun; Bosco, Dale B.; Ying, Yanlu; Tian, Dai-Shi; Wu, Long-Jun (Frontiers in Immunology, 2021)
Neuromyelitis optica (NMO) is an autoantibody-triggered neuro-inflammatory disease which preferentially attacks the spinal cord and optic nerve. Its defining autoantibody is specific for the water channel protein, aquaporin‐4 (AQP4), which primarily is localized at the end-feet of astrocytes. Histopathology studies of early NMO lesions demonstrated prominent activation of microglia, the resident immune sentinels of the central nervous system (CNS). Significant microglial reactivity is also observed in NMO animal models induced by introducing AQP4-IgG into the CNS. Here we review the potential roles for microglial activation in human NMO patients as well as different animal models of NMO. We will focus primarily on the molecular mechanisms underlying microglial function and microglia-astrocyte interaction in NMO pathogenesis. Understanding the role of microglia in NMO pathology may yield novel therapeutic approaches for this disease.